Impact of organizational culture on strategic planning. Issue 5 (16th July 2021) - Panda, Debadutta Kumar
Abstract : Purpose: The purpose of this paper is to examine the impact of organizational culture on strategic planning and the role of leadership effectiveness in the association between organizational culture and strategic planning in Indian nonprofit organizations (NPOs). Design/methodology/approach: Data were collected from 441 respondents using a structured questionnaire. Common method bias was addressed through the use of multiple surveys. Structural equation modeling was used to process the data. Findings: Advice-seeking interactions, collaborative culture and an error management culture positively impacted the creation and conceptualization of strategic plans in Indian NPOs. An error aversion culture did not significantly impact the creation and conceptualization of strategic plans. Leadership effectiveness moderated the relationship between "advice-seeking interactions" and the "creation and conceptualization" of the strategic plan, a "collaborative culture" and the "creation and conceptualization" of the strategic plan and an "error management culture" and the "creation and conceptualization" of the strategic plan. Originality/value: Strategic management literature on the determinants of the creation and conceptualization of strategic plans is scant. Further, it does not include the influence of cultural constructs such as advice-seeking interaction (ASI), collaborative culture (CC), error management culture (EMC), error aversion culture (EAC) on the creation and conceptualization of strategic plans. This study extends the debate on the culture–strategy nexus to help practitioners understand the importance of organizational culture (advice-seeking interaction, collaborative culture, error management culture, error aversion culture) in creating strategic plans.